New challenges in higher education and the CETYS Multiexperiential model - Rocha Beltrán, Lucía; Gárate Rivera, Alberto; León García, Fernando (My University, 2025)
This paper examines CETYS University's response to a changing and challenging educational landscape by implementing its Multiexperiential Educational Model, launched in 2023, driven by digital transformation and integrating advanced technologies, including artificial intelligence, micro-credentials, and experiential learning. This initiative aligns with the institution's 2036 strategic plan, guided by four fundamental pillars: fostering a culture of innovation, achieving significant impact, enhancing national and international relevance, and providing transformative experiences. In the wake of the pandemic in 2020, CETYS assessed the digital competencies of teaching staff and their adaptation to technology-driven teaching contexts following a strategic shift enabled by the Flex 360 model, which facilitated multimodal education amid forced classroom closures. This new educational framework, known by the community as CETYS Multiexperiential, addresses post-pandemic expectations of flexibility, expanded use of educational technology, and demands for enriched multimodal learning experiences. Innovative components such as virtual laboratories and micro-credentials have been incorporated to promote curricular flexibility and continuous skills development. This approach would allow CETYS to position itself as a transformative and adaptable higher education institution supported by humanistic and experiential learning principles.
Keywords: Digital transformation; Hybrid learning; Educational innovation; Experiential learning; CETYS multiexperiential model; Campus Ensenada